Contrôle de la conformité bactériologique du yaourt commercialisé et pouvoir conservateur du sirop de datte « Rob » sur les bactéries lactiques - NAAS Feriel, Amina; BOUHLALA, Marwa Asmaa (My University, 2021)
The present study works to valorize the processed food products of the dates, among which the valorization of the use of the date syrup having a low commercial value through its use for the preparation of yogurt. In this work, we used the syrup of a variety of dates known as "Hmira" as ingredients in the manufacture of a yoghurt. We have studied five types of yogurt each is prepared in different types of dosage of date syrup as follows: yogurt has 5 ml , 10 ml , 15 ml ,and has 20 ml of date syrup . The results of the microbiological analyzes of five yogurts clearly showed their perfect compliance with the standards. The organoleptic analyzes and the tasting test that we carried out for the five types of yogurts, were carried out with tasters, show an excellent acceptability of these yogurts.
Keywords: Yogurt , date syrup , date Hmira , organoleptic analyzes , tasting test , microbiological analyzes .